Pengembangan Sistem Notifikasi Informasi Terbaru PKBM Putra Peusangan Menggunakan Metode Agile - Marwan; Imam Muslem; Hannan Asrawi (Jurnal Ilmu Komputer Aceh, 2026)
The rapid development of information technology in education demands systems capable of delivering academic information quickly and accurately. One of the common problems at PKBM Putra Peusangan is the delay in delivering important information and student grades due to manual processes and limited communication media. This study aims to develop a web-based notification system integrated with a Telegram bot to automate the delivery of academic information to students. The system was developed using the Agile method to ensure flexibility and adaptability to user needs. Data processing is carried out through manual input and Excel file uploads, which are verified before being stored in the database. The results show that the system improves efficiency in information management and accelerates the delivery of notifications in real time. The implementation of this system makes information distribution more effective, transparent, and easily accessible for students.